Penyuluhan Program SPA (Sekolah Bebas Ispa) Kepada Siswa SD Galilea Hosana Kids School - Lumban Raja, Alex Maruli Tua; Siahaan, Dwi Lunarta Doderina; Jamnasi, Juli; Mega, Juli Yosa; Jeffrey, Jeffrey; Lim, Hadyanto; Herlen, Aldo; Gultom, Helmida; Koswara, Caroline; br. Sembiring, Rehulina; Sihite, Fiorella Natalia Kinanti; Dohude, Priscilla Putri Derlian; Brar, Dylan Amrirtraj; Fransella, Kezia; Panggabean, Kristina Dameria (Jurnal Pengabdian Pada Masyarakat METHABDI, 2024)
RTI (Respiratory Tract Infection) is an acute upper and lower respiratory tract inflammation caused by infectious agents, namely infections of microorganisms or bacteria, viruses, without or accompanied by lung parenchyma. RTI disease in Indonesia is on the 10th list of most common diseases in hospitals. PKM FK-UMI aims to bring the SPA (RTI-Free School/Sekolah Bebas ISPA) program, increase knowledge about RTI, and prevent and reduce the occurrence of RTI to Galilea Hosana Kids Elementary School. The method used is to deliver material about the definition, symptoms, how to get RTI, and how to prevent it. The results of the activity show that Galilea Hosana Kids Elementary School students still do not understand the meaning of RTI, the signs and symptoms of decreased body immunity, how to increase body immunity, and how to prevent the spread of RTI. Counseling for elementary school students at Galilea Hosana Kids Elementary School was very effective in educating students about RTI.